Natural history of liver disease in a large international cohort of children with Alagille syndrome: Results from the GALA study. Issue 2 (13th February 2023) - Vandriel, Shannon M.; Li, Li‐Ting; She, Huiyu; Wang, Jian‐She; Gilbert, Melissa A.; Jankowska, Irena; Czubkowski, Piotr; Gliwicz‐Miedzińska, Dorota; Gonzales, Emmanuel M.; Jacquemin, Emmanuel; Bouligand, Jérôme; Spinner, Nancy B.; et al.
Abstract : Background and Aims: Alagille syndrome (ALGS) is a multisystem disorder, characterized by cholestasis. Existing outcome data are largely derived from tertiary centers, and real‐world data are lacking. This study aimed to elucidate the natural history of liver disease in a contemporary, international cohort of children with ALGS. Approach and Results: This was a multicenter retrospective study of children with a clinically and/or genetically confirmed ALGS diagnosis, born between January 1997 and August 2019. Native liver survival (NLS) and event‐free survival rates were assessed. Cox models were constructed to identify early biochemical predictors of clinically evident portal hypertension (CEPH) and NLS. In total, 1433 children (57% male) from 67 centers in 29 countries were included. The 10 and 18‐year NLS rates were 54.4% and 40.3%. By 10 and 18 years, 51.5% and 66.0% of children with ALGS experienced ≥1 adverse liver‐related event (CEPH, transplant, or death). Children (>6 and ≤12 months) with median total bilirubin (TB) levels between ≥5.0 and <10.0 mg/dl had a 4.1‐fold (95% confidence interval [CI], 1.6–10.8), and those ≥10.0 mg/dl had an 8.0‐fold (95% CI, 3.4–18.4) increased risk of developing CEPH compared with those <5.0 mg/dl. Median TB levels between ≥5.0 and <10.0 mg/dl and >10.0 mg/dl were associated with a 4.8 (95% CI, 2.4–9.7) and 15.6 (95% CI, 8.7–28.2) increased risk of transplantation relative to <5.0 mg/dl. Median TB <5.0 mg/dl were associated with higher NLS rates relative to ≥5.0 mg/dl, with 79% reaching adulthood with native liver ( p < 0.001). Conclusions: In this large international cohort of ALGS, only 40.3% of children reach adulthood with their native liver. A TB <5.0 mg/dl between 6 and 12 months of age is associated with better hepatic outcomes. These thresholds provide clinicians with an objective tool to assist with clinical decision‐making and in the evaluation of therapies. Abstract :